Socioeconomic Environment and Obesity on the US West and East Coasts - Adrangi, Bahram; Hoppe, Athena; Raffiee, Kambiz (Journal of Social Economics Research, 2020)
The objective of this paper is to examine the association between obesity in the US West and East Coasts and access to grocery stores, fast food, convenience stores, recreational facilities, as well as the medium household income. A multivariate regression model based on aggregate county level observations for the West and the East Coasts based on the data from the US Department of Agriculture is estimated. Empirical results show that there is a positive association between obesity and convenience stores per county, while the rest of the variables showed negative association in the regression model. The elasticity between medium household income and obesity is the largest in magnitude for both geographic areas. These findings suggest policy recommendations for the short- and long-run that may be deployed to combat the obesity epidemic.